Interleukin 1 acts on cultured human vascular endothelium to increase the adhesion of polymorphonuclear leukocytes, monocytes, and related leukocyte cell lines. - Bevilacqua, M P (1985)
Increased leukocyte adhesion to the endothelial lining of blood vessels is an essential event in inflammation and the pathogenesis of certain vascular diseases. We have studied the effect of interleukin 1 (IL-1), an inflammatory/immune mediator, on endothelial-leukocyte adhesion using quantitative in vitro assays. Selective pretreatment of cultured human umbilical vein endothelial monolayers with IL-1 (5 U/ml, 4 h) resulted in an 18.3 +/- 2.6-fold increase in human peripheral blood polymorphonuclear leukocyte (PMN) adhesion (mean +/- SEM, n = 16) and a 2.6 +/- 0.3-fold increase in monocyte adhesion (n = 7) over basal levels. IL-1-treated endothelial monolayers also supported increased adhesion of the promyelocytic cell line HL-60 and the monocytelike cell line U937 (33.0 +/- 6.0-fold, n = 6 and 4.9 +/- 0.5-fold, n = 15, respectively). In contrast, selective IL-1 pretreatment of leukocytes, or the addition of IL-1 during the adhesion assay, did not alter endothelial-leukocyte adhesion. Conditioned medium from IL-1-treated endothelial cultures also did not promote leukocyte adhesion to untreated monolayers. IL-1 induction of endothelial adhesivity was concentration dependent (maximum, 10 U/ml), time dependent (peak, 4-6 h), and reversible, was blocked by cycloheximide (10 micrograms/ml) or actinomycin D (5 micrograms/ml) but not by acetylsalicylic acid (100 microM), and occurred without detectable endothelial cell damage. IL-1 treatment of SV40-transformed human endothelial cells and dermal fibroblasts did not increase their adhesivity for leukocytes. These data suggest that IL-1 can act selectively on human vascular endothelium to increase its adhesivity for circulating blood leukocytes, and thus to localize leukocyte-vessel wall interactions at sites of inflammation in vivo.